2020
DOI: 10.5469/neuroint.2020.00087
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Coincidental Free Floating Thrombus in the Vertebral Artery in a Patient Presenting with an Anterior Circulation Stroke and Literature Review

Abstract: Free-floating thrombus (FFT) is a rare condition with unknown etiology as described by many case reports presented in previous literature. The patients usually present symptomatically while the other few patients remain asymptomatic and are usually discovered incidentally on computed tomography angiography (CTA). Most of the cases reported in the literature are of FFT in the internal carotid artery. We present a 59-year-old female as a case of FFT in the vertebral artery which was coincidently discovered on CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“… 3 , 4 However, few asymptomatic cases were reported in the literature. 1 Our patient was symptomatic with recurrent strokes in the posterior circulation prior to therapy initiation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“… 3 , 4 However, few asymptomatic cases were reported in the literature. 1 Our patient was symptomatic with recurrent strokes in the posterior circulation prior to therapy initiation.…”
Section: Discussionmentioning
confidence: 78%
“… 9 Nevertheless, a successful surgical intervention via EVT in ICA-FFT and VA-FFT has also been reported. 1 , 11 A published review article by Bahtti et al 3 failed to show any superiority of either approach. As the therapeutic guideline for FFT has not been established yet, each patient should be approached, for the time being, individually in an interdisciplinary manner (neurology, neurosurgery, and neuroradiology) as we have done with our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 There have been several recent reports about the successful mechanical thrombectomy of CFFT. [6][7][8][9][10][11][12][13][14][15][16][17] These studies have demonstrated the challenges of safely performing mechanical thrombectomy due to significant clot burden, lack of tools, and techniques designed to perform cerebrovascular thrombectomy. In total, the literature to date has provided no conclusive techniques for safe and reliable removal of CFFTs.…”
mentioning
confidence: 99%
“…In total, the literature to date has provided no conclusive techniques for safe and reliable removal of CFFTs. 5,18 Recent technological improvements in aspiration catheters and stentrievers has made mechanical thrombectomy of cerebral vessels increasingly safe [6][7][8][9][10][11][12][13][14][15][16][17] and effective. 19,20 Among these developments are large-bore aspiration catheters (0.088" ID) 21,22 that are built both with and without compliant balloons for flow arrest and aspiration/flow reversal.…”
mentioning
confidence: 99%